Incidence and injury characteristics of traumatic brain injury: Comparison between children, adults and seniors in Israel. (2nd January 2016) - Siman-Tov, Maya; Radomislensky, Irina; Knoller, Nachshon; Bahouth, Hany; Kessel, Boris; Klein, Yoram; Michaelson, Moshe; Avraham Rivkind, Bala Miklosh; Shaked, Gad; Simon, Daniel; Soffer, Dror; Stein, Michael; et al.
Abstract: Aim : To assess the incidence and injury characteristics of hospitalized trauma patients diagnosed with TBI. Methods : A retrospective study of all injured hospitalized patients recorded in the National Trauma Registry at 19 trauma centres in Israel between 2002–2011. Incidence and injury characteristics were examined among children, adults and seniors. Results : The annual incidence rate of hospitalized TBI for the Israeli population in 2011 was 31.8/100 000. Age-specific incidence was highest among seniors with a dramatic decrease in TBI-related mortality rate among them. Adults, in comparison to children and seniors, had higher rates of severe TBI, severe and critical injuries, more admission to the intensive care unit, underwent surgery, were hospitalization for more than 2 weeks and were discharged to rehabilitation. After adjusting for age, gender, ethnicity, mechanism of injury and injury severity score, TBI-related in-hospital mortality was higher among seniors and adults compared to children. Conclusion : Seniors are at high risk for TBI-related in-hospital mortality, although adults had more severe and critical injuries and utilized more hospital resources. However, seniors showed the most significant reduction in mortality rate during the study period. Appropriate intervention programmes should be designed and implemented, targeted to reduce TBI among high risk groups.